DESCRIPTIVE MORPHOLOGY OF ATLAS BONES AND AXIS OF Chrysocyon brachyurus - Lobo-Guará (Illiger, 1815) - Pereira, Fabiano Borges (2020)
Chrysocyon brachyurus the Maned wolf is a wild canid from South America, found mainly in cerrado areas of Brazil. The knowledge gathered on the general and anatomical characteristics of wild animals collaborates for their conservation and maintenance of health. Therefore, the objective was to describe anatomically the structures of the Atlas and Áxis bones of C. brachyurus. The Atlas and Áxis vertebrae of C. brachyurus are similar to those of other canids, but with specific accidents, such as pointed transverse processes.